2018
DOI: 10.3389/fmicb.2018.01735
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-Like Systemic Inflammation Induced by Nano-Sized Extracellular Vesicles From Feces

Abstract: Nano-sized extracellular vesicles (EVs), including exosomes, microvesicles, and other types of vesicles, are released by most mammalian cells and bacteria. We here ask whether feces contain EVs of mammalian and/or bacterial origin, and whether these EVs induce systemic inflammation. Fecal extracellular vesicles (fEVs) were isolated from mice and humans. The presence of EVs from Gram-negative and Gram-positive bacteria was detected by enzyme-linked immunosorbent assay using anti-lipid A and anti-lipoteichoic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 43 publications
0
50
0
Order By: Relevance
“…We have shown that within 8 h of oral administration small numbers of labeled OMVs are evident in several organs and most notably the liver. In contrast to the parenteral administration of OMVs described in previous studies (Jang et al, 2015;Wiklander et al, 2015;Kim et al, 2017;Park et al, 2018), oral administration of Bt OMVs facilitates their interaction with the host GI-tract that is analogous to that of endogenously produced OMVs (Sonnenburg et al, 2005;Porter et al, 2017). The finding that the vast majority of Bt OMVs remain in the lumen of the GI-tract suggests that the general fate of OMVs generated in vivo is excretion.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We have shown that within 8 h of oral administration small numbers of labeled OMVs are evident in several organs and most notably the liver. In contrast to the parenteral administration of OMVs described in previous studies (Jang et al, 2015;Wiklander et al, 2015;Kim et al, 2017;Park et al, 2018), oral administration of Bt OMVs facilitates their interaction with the host GI-tract that is analogous to that of endogenously produced OMVs (Sonnenburg et al, 2005;Porter et al, 2017). The finding that the vast majority of Bt OMVs remain in the lumen of the GI-tract suggests that the general fate of OMVs generated in vivo is excretion.…”
Section: Discussionmentioning
confidence: 84%
“…Following our observation that Bt OMVs transmigrate across the intestinal epithelium, we sought to determine if after oral administration Bt OMVs could reach systemic tissues. Using an in vivo model adapted from those previously described (Park et al, 2010(Park et al, , 2018Jang et al, 2015;Wiklander et al, 2015;Kim et al, 2017), far-red fluorescent DiD-labeled Bt OMVs were orally administered to mice for 8 h prior to organ excision and imaging using a Bruker in vivo Xtreme imaging system. This time-point of tissue collection was optimal to observe the early stages of Bt OMV biodistribution to tissues via the blood stream.…”
Section: In Vivo Biodistribution Of Bt Omvs Following Oral Administramentioning
confidence: 99%
“…Paenalcaligenes hominis LPS was purified as described previously (Supplement Methods) [26]. FITC (F7250 Sigma, Aldrich)-conjugated EVs (FITC to protein ratio, 0.01) and LPS (FITC to LPS ratio, 0.1) were prepared as described by Park et al [48].…”
Section: Preparation Of Evs and Lps From Paenalcaligenes Hominismentioning
confidence: 99%
“…EVs are responsible for immune regulation, cell-to-cell interaction, and signal transmission by transporting bioactive molecules including proteins and lipids, DNA, and various RNAs, such as mRNAs, small-interfering RNAs (siRNAs), microRNAs (miRNAs), and long non-coding RNAs (lncRNAs) and other molecules produced by cells (132,(137)(138)(139). EVs can be detected in many organs, tissues, and all body fluids, such as urine, blood, and synovial fluid at low levels in physiological conditions (140,141). The increased levels of EVs are noted in cardiovascular disease, cancer, and pathological conditions that are associated with vasculitis: inflammation, autoimmunity, endothelial damage, angiogenesis, procoagulation, and intimal hyperplasia (131-133, 136, 140-142).…”
Section: Extracellular Vesicles In Primary Systemic Vasculitidesmentioning
confidence: 99%